2019
DOI: 10.5271/sjweh.3865
|View full text |Cite
|
Sign up to set email alerts
|

Do gender and psychosocial job stressors modify the relationship between disability and sickness absence: An investigation using 12 waves of a longitudinal cohort

Abstract: Do gender and psychosocial job stressors modify the relationship between disability and sickness absence: An investigation using 12 waves of a longitudinal cohort by Milner A, Aitken Z, Byars S, Butterworth P, Kavanagh A This study reports that workers with disabilities may be more likely to take sickness absence. Gender and job control are important considerations in understanding these absences. Modifying working conditions may therefore reduce the likelihood of workers with disabilities taking sickness abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Nonetheless, this still suggests that the mental health effect is nearly double the physical health effect. These results confirm previous findings from Australia [ 4 , 5 ] that a change in mental health is a significant predictor of workplace absenteeism, but for the first time we show the size of this effect relative to a change in physical health. This result for sickness absence is consistent with the health-related causes of permanent labour market exit in the UK, where mental health problems are now the most prevalent reason for claiming Employment Support Allowance [ 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, this still suggests that the mental health effect is nearly double the physical health effect. These results confirm previous findings from Australia [ 4 , 5 ] that a change in mental health is a significant predictor of workplace absenteeism, but for the first time we show the size of this effect relative to a change in physical health. This result for sickness absence is consistent with the health-related causes of permanent labour market exit in the UK, where mental health problems are now the most prevalent reason for claiming Employment Support Allowance [ 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some recent international research found that absence rates in Australia are about 5% higher among workers with poor mental health compared to those with good mental health, and that this is mitigated somewhat by increased job control and, for women, increased job security [ 4 ]. It has also been found that having a long-term health condition leads to a significantly higher rate of sickness absence in Australia, and this effect is higher for men and workers experiencing low job control [ 5 ]. In a study of six European countries (excluding the UK), people with severe disabilities had higher absence than non-disabled people, even controlling for indicators of short-term health state.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we utilized population-based twin cohort which adds to the earlier results based on occupational groups 9,30 . We also assume that our results shed further light to the findings that the associations between psychosocial working conditions and SA may not vary depending on definition of SA, 13,31 but more due to occupational groups, that is, many previous studies have been done on selected populations.…”
Section: Discussionmentioning
confidence: 74%
“…Studies vary on their definitions of SA both for duration and diagnosis groups, 9–11,16 but also vary their populations of interest, most commonly being focused on specific occupational groups 9,30 . It has been shown that the associations between psychosocial working conditions and SA may vary depending on definition of SA 13,31 …”
mentioning
confidence: 99%
See 1 more Smart Citation